2006
DOI: 10.1093/qjmed/hcl019
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of burnout and job satisfaction among Turkish physicians

Abstract: Organizational efforts aimed at increasing the level of job satisfaction among physicians could help to prevent burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
120
6
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 23 publications
12
120
6
18
Order By: Relevance
“…Although the literature shows gender as an important personal factor, studies in Turkey reveals no connection between job satisfaction and gender (33)(34)(35). The study conducted by Ünal found a higher level of life satisfaction for females, but our study results do not show such a relation (12).…”
Section: Discussioncontrasting
confidence: 85%
“…Although the literature shows gender as an important personal factor, studies in Turkey reveals no connection between job satisfaction and gender (33)(34)(35). The study conducted by Ünal found a higher level of life satisfaction for females, but our study results do not show such a relation (12).…”
Section: Discussioncontrasting
confidence: 85%
“…Our study included more than 90% of all residents who had received training in the area of pediatrics in Izmir at the time this study was conducted. Generally, the level of occupational exhaustion was found as high and the Burnout syndrome and reduced job satisfaction are observed in healthcare workers throughout the world and this condition is considered an occupational disease (2,(13)(14)(15)(16)(17). Emotional burnout is an internal dimension of exhaustion and individuals who experience this condition think that they are not sufficiently helpful for the people to whom they provide service.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that sex, age, the period of profession, familial structure, and the state of social support may affect the state of burnout (16,17). However, unexpected results may be obtained in healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Acil servis çalışanlarının KB düzeyi ile içsel, dışsal ve genel doyum düzeyleri arasında pozitif bir ilişki (r= 0.244; r= 0.361; r=0.168 p<0.05) olduğu bulgusu literatürle uyumludur.…”
Section: Discussionunclassified